2013
DOI: 10.1016/j.rbmo.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of GnRH agonist decreases oestradiol and VEGF concentrations in high responders

Abstract: This study evaluated whether the withdrawal of a gonadotrophin-releasing hormone (GnRH) agonist before triggering ovulation reduces the incidence of ovarian hyperstimulation syndrome (OHSS) in high-risk infertility patients who were treated with gonadotrophins. GnRH agonist was withdrawn for 2 or 3 days when dominant follicles were ≥14 mm in diameter, according to the GnRH agonist long protocol. Non-withdrawal of GnRH agonist was used as control. The serum concentration of oestradiol on the ovulation trigger d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
2
1
0
Order By: Relevance
“…Baseline characteristics and outcomes for the whole group are presented in Table 1. In this group of young women, the clinical pregnancy rate was 74.2%, whereas the live birth rate was 68.4%, which were consistent with our previous studies (Ding et al, 2013;Zhou et al, 2012Zhou et al, , 2013.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Baseline characteristics and outcomes for the whole group are presented in Table 1. In this group of young women, the clinical pregnancy rate was 74.2%, whereas the live birth rate was 68.4%, which were consistent with our previous studies (Ding et al, 2013;Zhou et al, 2012Zhou et al, , 2013.…”
Section: Resultssupporting
confidence: 92%
“…All patients received standard ovarian stimulation with recombinent FSH under pituitary suppression with GnRH agonist according to a routinely used protocol (Ding et al, 2013). In all women, pituitary desensitization was achieved by subcutaneous administration of triptorelin (0.1 mg daily, which was reduced to 0.05 mg after ovarian arrest was confirmed) started in the mid-luteal phase of the previous cycle.…”
Section: Ovarian Stimulation Protocolmentioning
confidence: 99%
“…These findings are consistent with earlier reports where luteal phase GnRH antagonist administration in patients, stimulated with either an agonist or an antagonist protocol, with established severe early OHSS seems to lead to quick regression of OHSS and avoidance of patient hospitalization [18,35]. Ding et al [36] reported that the withdrawal of GnRH agonist alone for 2 or 3 days in the late follicular phase in hyperresponsive agonist cycles markedly decreased the expression of CYP19A1, the production of oestradiol and VEGF mRNA concentration in granulosa cells, confirming the direct ovarian effect of GnRH agonist. Therefore, someone can assume that the administration of GnRH antagonist in the late follicular phase may directly block GnRH receptors on granulosa cells leading to a similar and maybe more profound effect on oestradiol and VEGF concentrations, as discontinuation of GnRH agonist does.…”
Section: Discussionsupporting
confidence: 92%